2004
DOI: 10.1051/vetres:2004028
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Salmonella status of market-age pigs and the pre-slaughter process on Salmonella caecal contamination at slaughter

Abstract: -The aim of this study was to evaluate the impact of the pre-slaughter process on Salmonella caecal contamination of pigs at slaughter. An observational study was carried out in 2001 on 101 conventional farrow-to-finish pig farms. On each farm, one batch of contemporary pigs was followed from the end of the fattening period until slaughter. The Salmonella bacteriological status of the batches was assessed by environmental samples of faecal material. The serological Salmonella status was obtained on 30 individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 35 publications
2
26
0
Order By: Relevance
“…It is clear that multiple intervention strategies are needed to effectively reduce the incidence of Salmonella contamination in processing plants (1,3,26). Toward this end, we hypothesized that phage therapy would prove very useful, as other groups have shown that phages can be used against difficult-to-treat infections, such as those caused by Pseudomonas and antibioticresistant tuberculosis (6,10).…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that multiple intervention strategies are needed to effectively reduce the incidence of Salmonella contamination in processing plants (1,3,26). Toward this end, we hypothesized that phage therapy would prove very useful, as other groups have shown that phages can be used against difficult-to-treat infections, such as those caused by Pseudomonas and antibioticresistant tuberculosis (6,10).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the proportion of pigs infected with Salmonella increases between the farm and the abattoir (Beloeil, Chauvin, et al, 2004;Gebreyes et al, 2004;Hurd et al, 2002). These observations reveal an effect of the pre-slaughter process, which includes handling, transportation, and lairage.…”
Section: From the Farm To The Abattoirmentioning
confidence: 95%
“…In general, S. Typhimurium was the most frequently isolated serovar followed by S. Rissen, a relevant serovar in Spanish pig farms (EFSA, 2008a;García-Feliz et al, 2007;Vieira-Pinto et al, 2005). S. Derby, a common serovar in other slaughterhouse studies (Beloeil et al, 2004;Botteldoorn et al, 2003;EFSA, 2008a;McDowell et al, 2007;Vieira-Pinto et al, 2005), and the monophasic variant of S. Typhimurium S. 4,[5],12:i:-, which has increased in prevalence in the latest decade (EFSA, 2010b;Hopkins et al, 2010), were also identified in a relevant number of samples. S. Bredeney was the fourth serovar identified in our study, although it should be pointed out that the 72 S. Bredeney isolates were all found in the same visit to slaughterhouse D (more than 70% of the Salmonella isolates recovered in that visit).…”
Section: ) Salmonella Contamination Is Particularly High In the mentioning
confidence: 98%